Effects of Kinesio tape on individuals with carpal tunnel syndrome: a randomized controlled study - Chen, Wei-Han; Chou, Willy; Hsu, Min; You, Yu-Lin; Wang, Yu-Lin; Cheng, Yuan-Yang; Lui, I-Ting; Liu, Chuan-Ching; Guo, Lan-Yuen (Frontiers in Rehabilitation Sciences, 2024)
ObjectiveCarpal tunnel syndrome (CTS) is a common neuromuscular disorder with an incidence rate of 4.9%. Research on the impact of Kinesio taping (KT) on electroneurography in individuals with CTS is limited, highlighting a significant gap in the literature. This study aimed to evaluate the effects of KT on palm numbness, pain intensity, hand grip strength, and median nerve electroneuromyography in individuals with mild to moderate CTS.MethodThis was a randomized, controlled, parallel design study. Twenty-seven participants diagnosed with CTS through hospital outpatient clinics were randomly assigned to either the control or KT group. The outcome measurements included hand grip strength, the Boston Carpal Tunnel Questionnaire (BCTQ), and electroneurography, assessed at baseline and after 6 weeks of intervention. The statistical method used was non-parametric analysis, comparing differences with the median and interquartile range (IQR).ResultsBoth the KT and control groups significantly improved the numbness grades, hand grip strength, and the BCTQ. The kinesio-taping group demonstrated an improvement in grip strength with a median increase of 2.21 kg (IQR: 0.65–3.79 kg), compared to the control group, which showed a median increase of only 0.70 kg (IQR: 0.22–1.45 kg). Statistical analysis revealed a significant difference between the two groups (p = 0.039), with an effect size of r = 0.33.ConclusionThis study suggested that KT can be a supplementary treatment to relieve pain intensity, enhance hand grip strength, and improve sensory conduction velocity, motor latency, and motor amplitude.Clinical Trial Registrationhttps://doi.org/10.1186/ISRCTN82192319, ISRCTNregistry (No. ISRCTN82192319).